1992
DOI: 10.1128/mcb.12.3.1330
|View full text |Cite
|
Sign up to set email alerts
|

Distal protein sequences can affect the function of a nuclear localization signal.

Abstract: The major DNA-binding protein, or infected-cell protein 8 (ICP8), encoded by herpes simplex virus can localize to the cell nucleus independently of other viral proteins. To define the nuclear localization signals within ICP8, we performed several forms of mutagenesis on the cloned ICP8 gene. Deletion analysis of the ICP8 gene showed that several portions of ICP8 are involved in its nuclear localization. To determine whether these regions were independent localization signals, we introduced various portions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…In contrast, VP-2 nuclear transport was halted by deletions created in any part of its sequence. While the activity of some NLSs is highly con- strained by a particular protein context (20,52), the extreme sensitivity of VP-2 nuclear transport to any deletion is unusual, an indication that this activity requires the correct cytoplasmic folding of the whole protein and hence its overall conformation. Indeed, wt and mutant VP-2 protein folding in the cytoplasm was verified by their ability to conform capsid epitopes in this compartment, while VP-1 protein appears unable to fold into similar structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, VP-2 nuclear transport was halted by deletions created in any part of its sequence. While the activity of some NLSs is highly con- strained by a particular protein context (20,52), the extreme sensitivity of VP-2 nuclear transport to any deletion is unusual, an indication that this activity requires the correct cytoplasmic folding of the whole protein and hence its overall conformation. Indeed, wt and mutant VP-2 protein folding in the cytoplasm was verified by their ability to conform capsid epitopes in this compartment, while VP-1 protein appears unable to fold into similar structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that not only residues 79 to 85 but also the IL-la precursor can translocate n-Gal to the nucleus. Indeed, it has been reported that sequences distant from the NTS can affect its ability to function (13). Moreover, it has been shown that acidic fibroblast growth factor (aFGF) contains a putative NTS which is able to direct the expression of ,-Gal to the nucleus; however, this NTS is unable to target either aFGF itself or an aFGF-1-Gal fusion protein to the nucleus, suggesting that aFGF contains an additional sequence which prevents endogenously expressed aFGF from being translocated into the nucleus (50).…”
Section: Discussionmentioning
confidence: 99%
“…The two identical NLSs KRRR of S6 represent a relatively strong signal because when this tetrapeptide is fused to 13-galactosidase it directs the hybrid protein exclusively into the nucleus (Figure 3). Efficiency of nuclear import can be influenced by the protein context of the NLS (Roberts et al, 1987;Nelson and Silver, 1989), by distant sequences (Gao and Knipe, 1992) …”
Section: Differential Import Efficiencies Of the Nlss Of S6mentioning
confidence: 99%